Desenvolvimento de um guia didático como estratégia pedagógica para o ensino sobre sistema imunológico e vacinas nas aulas de biologia - Aurino, Ana Nívea Batista (2024)
Advances in knowledge about immunology have encouraged the creation and improvement of several vaccines that contribute to the control of infectious diseases, constituting an important collective health tool. The Covid-19 pandemic has triggered expectations for scientific research in search of vaccines, seen as the most effective alternative in combating the health emergency. Therefore, approaching these themes during biology classes through investigative teaching and active methodologies can promote more meaningful learning and contribute to reducing students' susceptibility to non-scientific information about immunity and vaccination. The general objective of this work was to develop a teaching sequence on the immune system and vaccines through investigative teaching for the development of a teaching guide. It constituted a qualitative-quantitative and participatory research, carried out at the Pedro Pascoal de Oliveira State School, in Juazeirinho/PB, with 29 students from the 1st year of high school, between March and November of 2023. An Investigative Didactic Sequence (SDI) was carried out using the following methodological procedures: application of a Student Diagnostic Questionnaire (QDD), word cloud, conversation circle, flipped classroom, Participatory Integrated Panel (PIP), lecture, creation of models and didactic models, collective elaboration of national vaccination calendars, in addition to the creation of a didactic board game. Data analysis and discussion occurred in a qualitative and quantitative manner throughout each stage of the work. Data from the QDD, word cloud and conversation circle demonstrated that students had prior knowledge, although insufficient, regarding some content. The flipped classroom and PIP promoted investigative teaching and active methodologies that enabled students to identify the organs, tissues and cell types involved in the classification and physiology of immunity. The creation of models, didactic models, as well as the didactic game allowed students to take a leading role in developing pedagogical materials for teaching and learning about the immune system and vaccines. Holding a lecture and video exhibition about the PNI, as well as preparing basic vaccination calendars through tabulation on a poster, enabled the promotion of strategies that facilitated the recognition of the safety and effectiveness of vaccines for public health. This set of activities stimulated the practice of teaching through investigation and student protagonism through active methodologies, implicit objectives within the general proposal of this work, as well as the achievement of its general and specific objectives. From this perspective, this research had as its product a descriptive didactic guide on SDI applied as a pedagogical tool for knowledge about the immune system and raising awareness among students about the importance of vaccination. This work constitutes a contribution in this sense, but more studies need to be carried out within this perspective so that more materials on teaching the immune system and vaccines are produced and made available to teachers who wish to compensate for the superficial approach to this topic perceived in textbooks.